Meta Analisis Efktivitas Model Pembelajaran Numbered Head Together dan Jigsaw Terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran Matematika Kelas V - Pangestu Bagas Surya putra; Theresia Sri Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study uses a type of meta-analysis. The implementation was carried out from June to August 2021. The data analyzed were 20 articles, ten studies of the Numbered Head Together learning model and ten Jigsaw learning models. The average percentage of the NHT learning model from the low is 0.07% the highest is 55.55% the average is 219.06% While the percentage value of the Jigsaw learning model from the low is 1.22% and the highest is 7793% the average is 8045.49% The percentage value the Jigsaw model is high compared to the Numbered Head Together model. Calculation of the results of the hypothesis using the Ancova test, which is Univariate, states that the significance value is 0.327, meaning that it is greater than 0.05 (0.327 > 0.05). From the Ancova test, it states that f count > f table is 15,539 > 1,016 and a significance of 0, 327 > 0,05 which indicates that Ho is accepted and Ha is rejected. This shows that there is no significant difference in applying the Numbered Head Together and Jigsaw learning models to the critical thinking skills of fifth grade students in mathematics